E0044 The role of Ang1 and eNOS in the proangiogenic effect of simvastatin after myocardial infarction in rats. (17th November 2010) - Quan, He; Shu, Qin; Kanghua, Ma; Suxin, Luo; Xiaogang, Zhang
Abstract : Objective: To investigate the roles of angiopoietin-1 (Ang-1) and endothelial nitric oxide synthase (eNOS) in pro-angiogenic effect of simvastatin after experimental myocardial infarction (MI). Methods: 60 healthy adult SD rats were randomly divided into the sham operated group, control group, simvastatin group, simvastatin plus L-NAME (inhibitor of NOS) group and simvastatin plus AMG386 (inhibitor of Ang-1) group; Left anterior descending coronary was undergone permanent occlusion to establish the MI model. Rats with MI were administered simvastatin (1 mg/(kg·d)), simvastatin plus L-NAME (40 mg/(kg·d)), and simvastatin plus AMG386 (10 mg/(kg·wk)) respectively for 2 weeks. New microvessels in the ischaemic area near the infarction myocardium were stained by CD31 and the density of new microvessels was dedected; Ang-1, eNOS and phosphoralated endothelial nitric oxide synthase at Ser 1177 (p-eNOS) were evaluated by western blotting and RT-PCR assay. Results: (1) simvastatin significantly increased the density of new microvessels (p<0.05), but L-NAME and AMG386 significantly inhibited the pro-angiogenic effect of simvastatin (p<0.05). (2) simvastatin significantly improved The expression of Ang-1, eNOS and p-eNOS (p<0.05), and AMG386 significantly decreased simvastatin induced upregulation of p-eNOS. Conclusion: The pro-angiogenic effect of simvastatin is associated with increased expression of Ang-1, eNOS and p-eNOS, and phosphoralation of eNOS maybe the downstream pathway for Ang-1 induced angiogenesis.